Cytokine‐dependent regulation of dendritic cell differentiation in the splenic microenvironment. Issue 2 (12th December 2013) - Globisch, Theresa; Steiner, Nancy; Fülle, Lorenz; Lukacs‐Kornek, Veronika; Degrandi, Daniel; Dresing, Philipp; Alferink, Judith; Lang, Roland; Pfeffer, Klaus; Beyer, Marc; Weighardt, Heike; Kurts, Christian; et al.
<x xml:space="preserve">Abstract</x> The DC‐derived chemokine CCL17, a ligand of CCR4, has been shown to promote various inflammatory diseases such as atopic dermatitis, atherosclerosis, and inflammatory bowel disease. Under steady‐state conditions, and even after systemic stimulation with LPS, CCL17 is not expressed in resident splenic DCs as opposed to CD8α−CD11b+ LN DCs, which produce large amounts of CCL17 in particular after maturation. Upon systemic NKT cell activation through α‐galactosylceramide stimulation however, CCL17 can be upregulated in both CD8α− and CD8α+ splenic DC subsets and enhances cross‐presentation of exogenous antigens. Based on genome‐wide expression profiling, we now show that splenic CD11b+ DCs are susceptible to IFN‐γ‐mediated suppression of CCL17, whereas LN CD11b+CCL17+ DCs downregulate the IFN‐γR and are much less responsive to IFN‐γ. Under inflammatory conditions, particularly in the absence of IFN‐γ signaling in IFN‐γRKO mice, CCL17 expression is strongly induced in a major proportion of splenic DCs by the action of GM‐CSF in concert with IL‐4. Our findings demonstrate that the local cytokine milieu and differential cytokine responsiveness of DC subsets regulate lymphoid organ specific immune responses at the level of chemokine expression.